Autooxidation of Hemoglobins A and F after Freeze-Thawing - Timchenko, N. N.; Rozanova, E. D.; Kucherenko, Yu. V.; Leonov, B. N. (Problems of Cryobiology and Cryomedicine, 2002)
The authors studied the effect of freeze-thawing on structural and functional state of hemoglobins A and F. An increase in content of metforms in protein solutions is noted, which testifies to an acceleration of hemoglobins’ auto-oxidation. Conformation changes, accompanying this process, affect mainly the polar zones of molecules.